Peningkatan Kemampuan Pemecahan Masalah Dengan Menggunakan Model Talking Stick Berbantuan Video Pembelajaran - Hasanah, Siti; Wahyuni, Rahmi; Novianti, Novianti (Jumper: Journal of Educational Multidisciplinary Research, 2023)
The purpose of this study was to be able to determine the increase in problem-solving skills using the Talking Stick learning method better than what was taught through conventional learning with the help of learning videos on the material of a two-variable linear equation system in class VIII MTs Pandrah Private. The population in this study were all students of Class VIII MTsS Pandrah consisting of 2 classes totaling 26 students. The sample in this study were all fifth grade studentsA which totaled 13 students, VIIIB which totaled 13 students, Class VIIIA became an experimental class that was taught using Talking Stick learning and class VIIIB into a control class taught using conventional learning. Data collection techniques in the form of tests and observations. T test data analysis technique. The results of the analysis obtained the value of ttable this can be written as follows; ttable with a significance level of 5% = 1.303 < tcount equal to = 2.076 for tcount or ha accepted and ho rejected. It can be interpreted that increasing problem solving abilities using the Talking Stick learning method is better than what is taught through conventional learning with the help of learning videos on the material of a two-variable linear equation system in class VIII MTs Pandrah Private.